Usulan Perencanaan Sampling Penerimaan Berdasarkan Kecacatan Atribut dengan Metode Mil Std 105E pada Proses Penyamakan Kulit - Lobes Herdiman; I Wayan Suletra; Amithya Dwi Hapsari (Performa: Media Ilmiah Teknik Industri, 2008)
Plan acceptance of sampel with method of Military Standard 105E is prosedure which used in decision making to product yielded by company, background of this method him is to accommodate accomplishment of producer ekspektasi and consumer in inspection of[is quality of product with acceptance mechanism or deduction of lot. Pursuant to from amount of sampel proposals, existence of improvement of percentage of probability for normal inspection at quality of I mount 24% and quality of II mount 10%, tight inspection at quality of I mount 26% and quality of II mount 12%, diffuse inspection at quality of I mount 23% and quality of II mount 4%. While SOP proposal have the character of independent to the each category so that deduction of lot earn happened at every category not requiring accumulation of amount of found defect as SOP early.